‘Smart development’. An essay on a new political economy of the environment - Tausch, Arno (Munich, 2016)
"In this book, we present a first empirical reflection on ‘smart development’, its measurement and its possible ‘drivers’ and ‘bottlenecks’. We first provide cross-national data, how much ecological footprint is used in the nations of the world system to ‘deliver’ a given amount of democracy, economic growth, gender equality, human development, research and development, and social cohesion. To this end, we first developed UNDP-type performance indicators from current standard international comparative, cross-national social science data on these six main dimensions of development and on the combined performance on the six dimensions (a UNDP type ‘human development index plus’). We then show the non-linear standard OLS regression trade-offs between ecological footprints per capita and their square on these six components of development and the overall super-UNDP development performance index, derived from them. The residuals from these regressions are our new measures of smart development: a maximum of democracy, economic growth, gender equality, human development, research and development, social cohesion, and their combination with a minimum of ecological footprint. Our estimates underline the enormous importance of the positive effects of received worker remittances on smart development."